Therapeutic effects and potential mechanisms of astragaloside IV on pulmonary fibrosis: a systematic review and meta-analysis of preclinical studies - Zhang, Shujuan; Xue, Yan; Zhang, Xing; Chen, Feng; Li, Yalan; Zhang, Wei (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis (PF) remains a devastating disease with limited therapeutic options. Astragaloside IV (AS-IV), a natural compound from Astragalus mongholicus (AM), has shown promise as a possible treatment for fibrosis. However, a systematic evaluation of its therapeutic efficacy and underlying mechanisms is lacking. This meta-analysis synthesizes preclinical evidence to assess the therapeutic potential of AS-IV in PF.MethodsPreclinical literature published before 16 August 2024, was systematically retrieved and screened across eight major databases, including PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang Data Knowledge Service Platforms (Wanfang), China Science and Technology Journal Database (CQVIP), and China Biological Medicine Database (CBM). The risk of bias was assessed using the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) tool, and meta-analysis was conducted using STATA 18.0. The underlying mechanisms were also summarized.ResultsThis systematic review and meta-analysis encompassed 23 in vivo animal studies comprising a total of 518 animals. The methodological quality scores of the included studies ranged from 3 to 6 points. The overall analysis demonstrated that AS-IV significantly reduced key indicators of PF in animal models, including PF score [SMD = −2.56, 95% CI (−3.47, −1.65), P < 0.01, I2= 72.6%]; pulmonary inflammation scores [SMD = −2.18, 95% CI (−3.09, −1.27), P < 0.01, I2= 70.2%]; hydroxyproline (HYP) content [SMD = −4.31, 95% CI (−5.67, −2.95), P < 0.01, I2= 83.1%]; lung index [SMD = −3.43, 95% CI (−4.75, −2.10), P < 0.01, I2= 79.5%]; and α-smooth muscle actin (α-SMA) levels [SMD = −4.79, 95% CI (−6.01, −3.56), P < 0.01, I2= 55.3%]. Sensitivity analyses confirmed the robustness of these results. However, the asymmetry observed in the funnel plot suggests potential publication bias. Further analysis revealed that AS-IV modulates key biomarkers involved in the epithelial-mesenchymal transition (EMT) process and mitigates extracellular matrix (ECM) remodeling. Additionally, AS-IV reduces the levels of inflammatory markers and oxidative stress indicators, thereby exerting a significant intervention in PF.ConclusionThis meta-analysis demonstrates that AS-IV consistently ameliorates BLM-induced PF through multiple mechanisms, including inhibition of EMT, ECM remodeling, inflammation, and oxidative stress. These findings support further investigation of AS-IV as a multi-target therapeutic agent for PF.Systematic Review Registrationidentifier CRD42024604432.